2022
DOI: 10.3389/fneur.2022.913704
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment of aneurysms of the paraophthalmic segment of the internal carotid artery: Current status

Abstract: The paraophthalmic segment of the internal carotid artery (ICA) originates from the distal border of the cavernous ICA and terminates at the posterior communicating artery. Aneurysms arising from the paraophthalmic segment represent ~5–10% of intradural aneurysms. Due to the advent of endovascular treatment (EVT) techniques, specifically flow-diverting stents (FDSs), EVT has become a good option for these aneurysms. A literature review on EVT for paraophthalmic segment aneurysms is necessary. In this review, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 106 publications
(70 reference statements)
0
1
0
Order By: Relevance
“…A previous study found that endoleak can heal spontaneously at a high rate during follow-up. 20 According to our experience, once an endoleak occurs, we should be very careful to resolve it. Long-term blood leakage may lead to disastrous consequences.…”
Section: Discussionmentioning
confidence: 95%
“…A previous study found that endoleak can heal spontaneously at a high rate during follow-up. 20 According to our experience, once an endoleak occurs, we should be very careful to resolve it. Long-term blood leakage may lead to disastrous consequences.…”
Section: Discussionmentioning
confidence: 95%